Influencing the damage process and failure behaviour of polymer composites – A short review - Gergő Zsolt Marton; Gábor Szebényi (eXPRESS Polymer Letters, 2025)
Fibre-reinforced thermoset matrix polymer composites are gaining popularity in structural applications with strict quality requirements. However, their failure process, which is hard to predict and often catastrophic, mostly occurring at random locations, might be unfavourable in these areas. To ensure the further spread of composites and increase their reliability, their failure processes have to be influenced and controlled. This article gives an overview of different methods for influencing the damage process and failure behaviour of fibre-reinforced composite materials with thermoset polymer matrix. We describe the different methods, which can either control the failure in terms of location or mode or modify the failure behaviour, mostly by increasing toughness or achieving pseudo-ductile behaviour with a more gradual failure process. These methods can also simplify structural health monitoring, which has great importance in several applications of composite materials. The article focuses on the methods that enable the manipulation of the failure process by creating artificial damage or modifying the reinforcement, the matrix, the fibre-matrix interface, or the interlayer.